Inferior Alveolar Nerve Block: A Review of Alternate Techniques - Amrutha B. (Research Highlights in Disease and Health Research Vol. 7, 2023)
The aim of this present review was to describe anatomical variations of inferior alveolar nerve that could be encountered during surgical procedures there by avoiding surgical complications. Most common method for obtaining mandibular anaesthesia in dental practice is inferior alveolar nerve block though it has been estimated to have only 80 to 85% of success rate. The mandibular nerve and its branches are traditionally anesthetized by depositing anaesthetic fluid in the area of the mandibular foramen. This widely used procedure eliminates all somatosensory perception of the mandible, mandibular teeth, floor of the mouth, ipsilateral tongue, and all but the lateral (buccal) gingivae. The inferior alveolar nerve is known to present with anatomical variations prior to the nerve entering the mandibular canal, as well as along its course within the mandibular canal. In the case of difficulty-to-anesthetize patients, the inferior alveolar nerve can be especially tough. A sound knowledge of anatomical variations that could be encountered during surgical procedures is helpful in avoiding surgical complications. In such situations the alternatives to inferior alveolar nerve block described in this article can be successfully utilised with the best knowledge and skill of the operators.